GREENING HOSPITALITY HUMAN RESOURCE: A SYSTEMATIC LITERATURE REVIEW. - Choudhary, Parul; Datta, Amit (The journal of contemporary issues in business and government, 2022)
Green human resource management (Green HRM) is a well-accepted norm in institutions that promote and practice activities for the conservation of the environment to support ecological balance. This study is the first attempt to explore the Green HRM ecosystem in the hospitality industry. Systematic literature review of publications in Scopus-listed journals has been the base methodology used to tie conceptual strings between the constructs by evaluating literature with respect to the hospitality industry. The paper adds a detailed conceptual framework to existing Green HRM literature and lays a foundation for future research agendas in Greening human resource management in the hospitality industry.